No Pay for Sexist Performance: How Gender Disparities in Healthcare Hurt Hospitals’ Pay for Performance Reimbursements - Emily C. Bartlett (Washington University Law Review, 2018)
Gender disparities and discrimination in healthcare treatment are vast. Women in pain are deemed hysterical, heart attacks in women are caught less frequently than in men due to symptom presentation differences, and women are screened less often than men for some cancers. Meanwhile, in order to be fully reimbursed for healthcare services, legislative reforms increasingly evaluate hospitals and physicians based on their performance as it relates to quality measurements, otherwise known as pay for performance. This particular method of reimbursement expanded after the Patient Protection and Affordable Care Act (ACA) enacted pay for performance standards, particularly for hospitals and physicians participating in Medicare. The pay for performance standards included in the ACA were a missed opportunity to explicitly name and address existing gender disparities in healthcare. For example, the ACA evaluates and potentially penalizes hospitals and doctors based on their quality standards with acute myocardial infarctions (commonly known as heart attacks). When hospitals actively fail to diagnose and to treat heart attacks in women, they may be losing reimbursement money under the ACA. However, the language of the ACA hides the gendered aspect of this loss. Gender disparities and discrimination in healthcare negatively impact pay for performance reimbursements for both hospitals and physicians and result in hospitals losing reimbursement payments, especially via Medicare. To ensure better quality healthcare for female patients and maximum reimbursement levels for hospitals and physicians providing Medicare services, this Note will examine two categories of possible solutions: legislative and ground-based. First, Congress could amend the ACA and its Medicare provisions to explicitly call for reductions in gender-based healthcare disparities. Second, hospitals throughout the country could implement ground-based efforts such as unconscious bias training for all healthcare providers. This Note adopts feminist legal theory as a lens through which to view the problem of gender disparities in healthcare and pay for performance reforms by asking about gender implications of a law, thus asking “the woman question” (“Woman Question”). Specifically, this Note asks how and why the ACA fails to adequately address gender-based disparities in healthcare. This question presumes the current law is non-neutral and seeks to “expose those features and how they operate” before turning to potential solutions. A non-neutral law may appear on its face to be neutral towards women and men, but affect women and men differently. Asking the Woman Question in the context of gender disparities and pay for performance reform reveals how women’s healthcare “reflects the organization of society rather than the inherent characteristics of women.” Analyzing the ACA through a feminist lens requires a look “beneath the surface” of the law to identify its gender implications. Framing the analysis in this way does not necessitate a solution which favors women but requires a “decision . . . that is defensible in light of [gender] bias.” Part I of this Note examines the existing gender disparities in healthcare, especially in the areas of cardiovascular disease, pain management, and cancer. Part II analyzes pay for performance reforms in the ACA. First, Part II looks at the Affordable Care Act generally. Then, Part II turns to the Medicare reforms in the ACA, focusing on the Hospital Readmissions Reduction Program and the Hospital Value-Based Purchasing Program. Part III integrates gender-based disparities in healthcare and pay for performance reforms, proposing solutions at both the legislative and ground-based levels. The Note argues that if hospitals prompted their physicians to consider, for example, the differences in how women and men present with heart attacks, the hospitals’ scores on pay for performance quality measures would rise. This in turn would mean higher reimbursement for hospitals, many of which desperately need reimbursement funds to remain in business.
Keywords: Gender disparities; Gender discrimination; healthcare; health law; Patient Protection and Affordable Care Act; Affordable Care Act; ACA; Obamacare; pay for performance; Medicare; feminist legal theory; Woman Question; reimbursement; Cardiovascular Disease; CVD; pain management; cancer; women; Readmissions Reduction Program; Hospital Value-Based Purchasing Program; HVBP